IDENTIFICATION OF BACTERIA CAUSING NECROTIC PULP WITH 16S rRNA GENE POLYMERASE CHAIN REACTION AND ANTIBIOTIC RESISTANCE TESTING AT THE DENTAL HOSPITAL IN SEKELOA, BANDUNG, INDONESIA - Rostinawati, Tina; Hadisoebroto, Sulistiyaningsih; Iskandar, Yoppi; Nugroho, Prasetyo Hadi; Tara, Audria Amanda (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aims to identify the bacteria that cause necrotic pulp in teeth of dental patients and test resistance of the bacteria found to antibiotics. Methods: Bacteria were taken with paper points that were inserted into the root canal of patients at the Dental Hospital of the Faculty of Dentistry, Universitas Padjadjaran, Sekeloa, Bandung. Bacteria were cultured and Gram-stained. Bacterial DNA was isolated to be identified by polymerase chain reactions 16S rRNA method against known sequences of bacterial DNA. Then, identified bacteria were tested for antibiotic resistance to tetracycline (30 Î¼g), clindamycin (2 Î¼g), amoxicillin (10 Î¼g), and ampicillin (10 Î¼g). Results: The 16s rRNA gene fragment of the main bacterium found was in 98% homology with 16S rRNA gene database in http://blast.ncbi.nlm. nih.gov, i.e., Pseudomonas aeruginosa and Acinetobacter schindleri. The results from inhibition zone of each antibiotic were 20.12 mm, 8.97 mm, 8.12 mm, and 8.03 mm for tetracycline, clindamycin, amoxicillin, and ampicillin, respectively, to P. aeruginosa. While inhibition zone of tetracycline to A. schindleri was 37.7 mm. Conclusion: Based on the study results, P. aeruginosa from patients with necrotic pulp samples were resistant to clindamycin, amoxicillin, ampicillin, and decreased activity to tetracycline. While Acinetobacter schindleri was still sensitive to tetracycline.